2018
DOI: 10.1016/j.ijpddr.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Cos-Seq screen with intracellular Leishmania infantum for the discovery of novel drug-resistance mechanisms

Abstract: Increasing drug resistance towards first line antimony-derived compounds has forced the introduction of novel therapies in leishmaniasis endemic areas including amphotericin B and miltefosine. However, their use is threatened by the emergence and spread of drug-resistant strains. In order to discover stage-dependent resistance genes, we have adapted the Cos-Seq approach through the introduction of macrophage infections in the pipeline. A L. infantum intracellular amastigote population complemented with a L. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…Different parasite molecular modifications, such as ABC transporters, membrane composition changes or oxidative stress, among others, can contribute both directly and indirectly to the phenomena of drug resistance [35,46,58]. Moreover, it has been shown that Leishmania is able to actively alter macrophage and neutrophil environments to resist current antileishmanial agents [59].…”
Section: Discussionmentioning
confidence: 99%
“…Different parasite molecular modifications, such as ABC transporters, membrane composition changes or oxidative stress, among others, can contribute both directly and indirectly to the phenomena of drug resistance [35,46,58]. Moreover, it has been shown that Leishmania is able to actively alter macrophage and neutrophil environments to resist current antileishmanial agents [59].…”
Section: Discussionmentioning
confidence: 99%
“…LRR protein is an important gene in antimonial resistance in Leishmania spp. [26]. This gene is located in chromosome 6.…”
Section: Resultsmentioning
confidence: 99%
“…All these studies have used the extracellular promastigote stage as it is known to be easier and faster. Only two studies opted to use intracellular amastigotes for the selection of cosmid bearing parasites [ 113 , 116 ], resulting in the identification of predominantly different genes compared to those identified in promastigotes [ 116 ]. These differences could be caused by a number of factors, not necessarily directly related to the drug, such as the host cell environment, parasite infectivity and intracellular multiplication [ 116 ].…”
Section: Genome-wide Expression Studiesmentioning
confidence: 99%